Penentuan Dimensi Meja Dan Kursi Yang Ergonomis Dengan Metode Antropometri Dan Menggunakan Data Statistik Analisis - Dini Syahriza Fahlevi; Iskandar Iskandar; Mohd. Iqbal (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
This study took place in High School (SMA) dispersed in Pidie District, Aceh, with the object of obser-vation is support facilities and learning activities in the classroom, namely chairs and desks. This re-search was done in three stages: initial analysis stage by using Catia software and to use the RULA (Rapid Upper Limd Assessment) analysis. The second stage is the anthropometric data collection where the sample was taken 30 students per high school of 10 students divided into grade 1, 10 students in grade 2, and 10 students in grade 3. The final stage is the stage of anthropometric data processing, in this study data using statistical analysis. Design concepts and ideas are expected to produce a design that suits your needs and can represent antropomeri high school students Pidie district, Aceh. A proto-type chairs and tables will also be displayed as a result of this study taking into account aspects of com-fort with changing height, seat width, backrest tilt, and the addition of the supporting hand.